2011
DOI: 10.5251/abjna.2011.2.6.887.896
|View full text |Cite
|
Sign up to set email alerts
|

Soil nutrient status and productivity potentials of lithosols in Mubi Area, Northeastern Nigeria

Abstract: Continuous and coherent hard rock between 10.0 and 50.0cm of topsoil can considerably impede crop production. A field survey was conducted in 2006 to assess the physico-chemical properties, Fa and Pp of lithosols from six locations (Muvur, Digil, Vimtim, Gella, Lamorde, and Madanya) in Mubi area, Northeast Nigeria. Soils were sampled at 0-20, 20-50, and 50-100 cm depths in each of the six locations for the analyses of particle size distribution, bulk density, water holding capacity, pH, EC, OC, %N, avail P, K,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…Organic matter had high variation (≥40.08 % ≤ 83.14 %) in pedons 2 and 3 and low variation (13.70 %) in pedon 1. However, organic matter content was high compared to the finding of Tekwa et al (2011) in soils of Northern, Nigeria. Organic matter improves the soil structure thereby reducing the erodi-bility rate of the soil.…”
Section: Soil Chemical Properties and Micronutrientsmentioning
confidence: 55%
See 1 more Smart Citation
“…Organic matter had high variation (≥40.08 % ≤ 83.14 %) in pedons 2 and 3 and low variation (13.70 %) in pedon 1. However, organic matter content was high compared to the finding of Tekwa et al (2011) in soils of Northern, Nigeria. Organic matter improves the soil structure thereby reducing the erodi-bility rate of the soil.…”
Section: Soil Chemical Properties and Micronutrientsmentioning
confidence: 55%
“…Total nitrogen and available phosphorus had high variation (≥40.08 % ≤ 83.14 %) in all the pedons except in pedon 3 where total nitrogen had low variation (5.89 %). The total nitrogen was high while the available phosphorus was low compared to the find-ing of Tekwa et al (2011) and Musa and Gililanbe (2017) in soils of Northeast Nigeria. The Table 2 showed that potassium was predominant over other cations in pedons 1 and 2 while Magnesium was predominant in pedon 3.…”
Section: Soil Chemical Properties and Micronutrientsmentioning
confidence: 64%
“…Generally the P H range is between 5.09-5.96 with a mean of 5.36, indicating that the soil was slightly acidic (Tekwa et al, 2011). The soil OM generally varies in depletion with soil depths as observed by Brady and Weil, 2002.…”
Section: Nutrients Requirements Of Maizementioning
confidence: 66%
“…Organic matter concentration, available nitrogen, available phosphorus, total exchangeable bases and acidity, and effective cation exchange capacity (ECEC) all indicated low values in this soil. For instance, both available nitrogen and available phosphorus were below their critical ranges of values of 1.50-2.00 and 10-16 mg kg -1 , respectively for arable crop production in tropical soils (Sobulo and Osiname 1981;Adeoye and Agboola 1985). Similarly, the soil was deficient of exchangeable potassium, as this parameter was clearly below the critical range of values of 63-99 mg kg -1 (Akinrinde and Obigbesan 2000).…”
Section: Resultsmentioning
confidence: 99%